DEPENDENCIES BETWEEN MORPHOLOGICAL INDICATORS AND EARLY RIPENESS OF GREENHOUSE TOMATOES AT DIFFERENT LEVELS OF FERTILIZATION AND DILFERENT WATER SUPPLY - A. Stoyanova; V. Kuneva; M. Georgiev; N. Valchev (Trakia Journal of Sciences)
The purpose of this study is to determine the impact of controlled permanent water deficiency and three levels of fertilization on earliness and total yield of tomatoes, greenhouse production using different mathematical approaches. In order to evaluate the morphological manifestations, the early harvest and the total yield under the influence of different irrigation and nutritional regimes, a tomatoes variety "Vitelio" was used. The irrigation is done with a drip irrigation system. Against the background of the same fertilizing rates in the variants with different irrigation norms there is a decrease in the early stage with an increase of the irrigation norms. A high correlation between plant height and total yield, with correlation coefficient (r = 0.899) and between sheet count and total yield r = 0.824 was found. There was a negative correlation between the first and third harvests and the total yield, respectively with correlation coefficients r = -0.724 and r = -0.704. The nature of the linear relationship between plant height and total yield is determined by the coefficient R2 = 0.8. Based on a two-factor analysis, it was found that irrigation regime had a dominant influence on the two parameters considered: height and yield, which was statistically proven with a very high degree of confidence (p ≤ 0.001).